Tingkat Pengetahuan Dan Presepsi Masyarakat Muslim Mengenai Pengobatan Menggunakan Zat Yang Haram Di Lingkungan Masyarakat Rt 12 Rw 03 Kelurahan Kebun Beler Kota Bengkulu - Nanik; Muhammad Alfi Ash-Shidiqy (Yayasan Darusssalam Bengkulu, 2025)
Nowadays, a product's halal status is crucial, particularly for Indonesia, where the majority of people are Muslims. Choosing halal items is becoming more and more important in Muslim society. Muslim customers will learn more about the religion and inform manufacturers about halal certifications so they are aware of the importance of consuming halal products. The public is becoming more interested in halal items. Onething, medicine, is still reasonably priced, though. The actions of the Muslim community are inextricably linked to their degree of knowledge, awareness, and comprehension regarding halal items. Thus, this study aims to provide an overview of the public's knowledge, attitudes, and perceptions of halal health in RT 12 RW 03 Kebun Beler Village, Bengkulu City. This study used a descriptive, observational approach model (rather than an experimental one). The Muslim community in RT 12 RW 03 Kebun Beler Village, Bengkulu City, will be sampled using the purposive sampling technique. when employing a survey to gather data. According to the study's findings, 51% of the population had a moderate level of knowledge, awareness, and attitude toward halal medicines, 53% had a very good level, and 53% had a very high level. We can infer that public understanding is in the intermediate range, despite the fact that attitudes and awareness of halal medications are excellent.